Octreotide in the management of chemoradiotherapy-induced diarrhea refractory to loperamide in patients with rectal carcinoma - Topkan, Erkan; Karaoglu, Aziz (Karger, 2006)
Objective: To evaluate the efficacy of octreotide in the treatment of chemoradiotherapy ( CRT)- induced diarrhea ( CRTID) refractory to conventional loperamide treatment in this pilot study. Methods: Forty- two rectal carcinoma ( T3-4N0-2M0) patients with grade 2 or 3 diarrhea refractory to loperamide were enrolled to receive octreotide. Eligible patients were treated with pelvic radiotherapy combined with bolus 5-fluorouracil CRT. Octreotide was administered subcutaneously, 150 mu g three times daily, for 5 consecutive days. Only complete resolution of diarrhea was considered as therapeutic success. Results: Diarrhea mainly occurred in the first 4 weeks of CRT ( 83.3%) and completely resolved in 34 patients ( 80.9%) following octreotide administration. Mean time to response was 2.7 days: 27 patients ( 64%) responded during the first 3 days, and the remaining 7 ( 17%) on days 4 and 5. No significant side effect was reported. Eight patients ( 19.1%) with refractory diarrhea were hospitalized for additional treatment. No treatment delay was reported in complete responders, whereas an average 7.7- day delay was observed in refractory patients. Antidiarrheal treatment was administered on an outpatient basis in the response group, whereas refractory patients were hospitalized for an average of 8.8 days. Conclusion: Daily subcutaneous octreotide administration ( 150 mu g t.i.d.) for 5 days is apparently an effective, tolerable treatment modality for concurrent CRTID refractory to loperamide. Copyright (C) 2006 S. Karger AG, Basel.
Keywords: chemoradiotherapy; loperamide; octreotide; refractory diarrhea